Perceived discrimination as a mediator between cultural identity and mental health symptoms among racial/ethnic minority adults in the United States: insights from the Health Information National Trends Survey 6 - Zhou, Lulin; Nutakor, Jonathan Aseye; Larnyo, Ebenezer; Addai-Dansoh, Stephen; Cui, Yupeng; Dey, Nutifafa Eugene Yaw (Frontiers in Psychology, 2024)
Objective: This study examined the role of perceived discrimination as a mediator between cultural identity and mental health symptoms among adults from racial/ethnic minority groups in the United States.Methods: Data were gathered from the National Cancer Institute's (NCI) Health Information National Trends Survey (HINTS) 6, a nationally representative survey. The mediating role of perceived discrimination was investigated using structural equation modeling (SEM) analysis.The study found significant associations between demographic and lifestyle factors and mental health symptoms. Non-Hispanic Blacks or African Americans and Hispanics were less likely than Non-Hispanic Whites to have mental health symptoms. Individuals between the ages of 35 and 49, 50 to 64, 65 to 74, and 75 and older had lower odds of mental health symptoms. Gender differences revealed that females had a higher risk of mental health issues than males. Socioeconomic factors, such as household income and employment status, played a significant role, with higher household income and employment status being associated with a decreased likelihood of mental